Diamove: associação entre medidas de função e estrutura muscular diafragmática e periférica com desfechos de pacientes ventilados mecanicamente - Costa, Roberta Catunda (2024)
Introduction: Variables obtained through ultrasonography (US) have been widely studied in the Intensive Care Unit (ICU) for their predictive capacity regarding negative outcomes, such as reintubation, and their correlation with other functional muscle assessment tools. Despite the availability of several methods to evaluate the performance of inspiratory muscles in the ICU, assessing dynamic aspects remains challenging. The Test of Incremental Respiratory Endurance (TIRE) includes variables for assessing dynamic pressures and muscle fatigue, showing promise in this context. Objectives: To investigate the association between ultrasonographic measurements obtained after orotracheal intubation and negative clinical outcomes, such as dependence on mechanical ventilation (MV), the need for tracheostomy (TQT), and mortality, and to explore their correlations with TIRE variables obtained after extubation. Methods: This prospective cohort study included individuals aged over 18 years and under 85 years, who were mechanically ventilated due to respiratory failure caused by clinical conditions, with a history of prior functional independence. The variables diaphragm thickness (DT) and rectus femoris cross-sectional area (RF CSA) were measured using US; handgrip strength (HGS) was assessed with a portable dynamometer; TIRE was performed using the PrO2 portable pressure manometer; and mobility was evaluated using the ICU Mobility Scale (IMS). US measurements were conducted within 36 hours after intubation, 7 days after intubation, and within 24 hours after extubation. HGS and TIRE assessments were conducted post-extubation, while IMS evaluation was performed upon ICU discharge. The negative outcomes measured included reintubation, MV duration exceeding 14 days, the need for tracheostomy (TQT), mortality, and the presence of at least one of these outcomes. Results: The study included 49 participants, 59.2% of whom were male, with a mean age ± standard deviation of 67.79 ± 15.35 years. A comparison of mean DT values measured after 7 days of MV showed significant associations with negative outcomes such as MV dependence (p = 0.02) and the need for TQT (p = 0.01). Similarly, RF CSA measured on the same day was associated with the same outcomes. Diaphragmatic thickening fraction (DTF) was identified as significant for predicting reintubation and mortality, both in mean comparisons and in binomial logistic regression modeling. After extubation, 22 individuals were eligible for TIRE testing, which was correlated with US, HGS, and IMS variables. Among the TIRE variables, Sustained Maximum Inspiratory Pressure (SMIP) and, particularly, the Fatigue Index Test (FIT) showed moderate to strong correlations with variables such as DT (rs = 0.56, p = 0.03), HGS (rs = 0.51, p = 0.04), and IMS (rs = 0.51, p = 0.04). Conclusion: The results suggest that combined assessments of peripheral and diaphragmatic muscles, even after several days of MV, can be useful in predicting negative outcomes in intensive care. Post-extubation, TIRE-derived variables appear promising for monitoring and evaluating functional capacity.